Smart Agribot: Advanced CNN-Based Disease Detection in Green Beans with EfficientDet & Auto-Spraying - Froilan G. Destreza; Romeo Concepcion Jr.; Jomari A. Alano; Joven J. De Padua; Ken J. Butiong (International Journal of Integrated Engineering, 2025)
The Smart Agribot is a cutting-edge robotic system developed to improve how green beans are grown in the Philippines. It combines advanced technology like Convolutional Neural Networks (CNNs) for disease detection, automated spraying, and efficient crop transportation. This project aims to make farming more productive, reduce waste, and improve plant health. The Agribot’s physical design uses common, affordable parts like Arduino Uno, Raspberry Pi, metal frames, and wooden supports, creating a sturdy yet cost-effective machine. Its brain is a CNN model trained on a large set of images showing healthy and diseased green bean plants. This training allows the Agribot to accurately identify different plant diseases. Extensive testing confirmed that the system can reliably detect diseases, with especially high accuracy in spotting Rust, a common issue in bean crops. The Agribot’s automatic sprayer further reduces the amount of chemicals needed by only spraying plants that truly need it, which lowers costs and lessens environmental harm. Additionally, the built-in crop transporter makes harvesting faster and more efficient without significantly affecting crop yields. Together, these features make the Smart Agribot a promising tool for modern farming. It can help farmers save time, reduce costs, and improve overall productivity. As the Agribot continues to be improved, it has the potential to work with other crops and farming systems, supporting more sustainable agriculture in the future.